SOFT SKILLS DALAM PEMBELAJARAN DOKKAI - Noviana, Fajria (Vocational College of Diponegoro University, 2017)
Learning process in universities in Indonesia today have not give the students balanced competencies in soft skills (such as communication, adaptation, leadership, teamwork, etc) and hard skills yet, because the lecturers tend to focuse on hard skills’ competencies only. Some students who don’t realize the soft skills’ competencies in learning foreign language and literature has made this worse. Therefore, this paper attempt to present to lecturers and students about how soft skills’ competencies can be presented in foreign language and literature learning. With Action Research’s method, in once reading learning of Diponegoro University Japanese Study Program’s 3rd grade students, the enhancement of students’ compentencies in soft skills can be known. The result is, competencies in soft skills’ teaching material can be added in language and literature learning.